The Congenital Diaphragmatic Hernia Study Group Registry - Morini, Francesco; Lally, Pamela A.; Lally, Kevin P.; Bagolan, Pietro (European Journal of Pediatric Surgery, 2015)
Congenital diaphragmatic hernia (CDH) is a rare anomaly with an incidence between 1/2,500 and 1/3,000 live births. The rarity of the disease makes it difficult to design powerful studies leading to accurate and meaningful evidence. For rare diseases, the development of multicenter international registries may help in collecting data and give an overall picture of the disease. In this review, we will describe the development of the CDH study group, we will describe its work methodology, and the results obtained since its birth in 1995.
Keywords: congenital diaphragmatic hernia; management; registry; stratification; treatment